REPRODUCTIVE PERFORMANCE IN RESPONSE TO DIFFERENT HORMONAL TREATMENTS IN LOCAL GOATS - Bamerny, Araz O.; Alkass, Jalal E.; Barwary, Mwafaq S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
To evaluate the effect of different hormonal treatments on reproductive performance of local goats, 60 adult does were synchronized by using sponges impregnated with 40 mg medroxy acetate (MAP) for 14 days. Following sponges withindrawn, the does were allocated randomly to four equal groups. The first group was served as control and intramuscularly injected with normal saline (T1). The does in group 2,3  and 4 were injected intramuscularly with 250 i.u hCG(T2) 400 i.u. eCG(T3) and 20 µg GnRH(T4), respectively. Results revealed that the highest estrus response was recorded in T2 (100%) followed by T4(93.3%), T1 (86.7%) and T3(73.3%). Fertility rate was significantly (p˂0.05) higher in T4 (93.3%) and the lowest was found in T3 (66.7%). A significantly higher kidding rate (146.7%) and litter size (1.69) was recorded in T2. While the lowest kidding rats and litter size was recorded in T4 and T3, respectively.